2005
DOI: 10.1200/jco.2005.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Type Soft Tissue Sarcomas in Pediatric-Age Patients: Experience at the Istituto Nazionale Tumori in Milan

Abstract: The identification of prognostic variables should enable risk-adapted therapies to be planned. Patients with initially unresectable disease and patients with resected large and high-grade tumors are at high risk of metastases and treatment failure. Although the limits of this retrospective analysis are self-evident, our data would suggest that intensive chemotherapy (with an ifosfamide-doxorubicin regimen) might have a more significant role in these patients than what is generally assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 31 publications
7
124
4
1
Order By: Relevance
“…By multivariate analysis, we found that local disease, NR-STS histology, and surgical resection were all independent prognostic indicators of survival for extremity tumors. These findings have been corroborated by other groups [4,5,7,8,16]. In addition, we found that muscle (not synovial sarcoma) and nerve tissue origin was an indicator of poor outcome, while adipose and fibrous origin predicted improved survival.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…By multivariate analysis, we found that local disease, NR-STS histology, and surgical resection were all independent prognostic indicators of survival for extremity tumors. These findings have been corroborated by other groups [4,5,7,8,16]. In addition, we found that muscle (not synovial sarcoma) and nerve tissue origin was an indicator of poor outcome, while adipose and fibrous origin predicted improved survival.…”
Section: Discussionsupporting
confidence: 84%
“…In our cohort of 1175 patients with extremity STS, we confirmed that most are NR-STS and present in patients older than 10 y of age [4,5,8]. In contrast, RMS were more prevalent in younger patients with alveolar type as the most common histologic subtype [8].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Pediatric NRSTS have been considered as orphan diseases: despite the global incidence of NRSTS falling only a little short of the figure for RMS, the published studies available on pediatric NRSTS are far less numerous than those on RMS [12,13,[19][20][21][22][23][24][25][26], and most of the experience gained on the treatment of pediatric NRSTS has been based on principles derived from the management of RMS, which is a clearly distinct entity.…”
Section: Introductionmentioning
confidence: 98%
“…Because they represent a diversity of originating tissues, they have distinct biology, and therefore respond differently to therapy [1][2][3][4]. Some of the sarcomas commonly seen in children are also present in adults [5], which allow the pediatric therapies to exploit knowledge developed in adults with the same tumor types. As a result of their diverse biology, conventional therapeutics for pediatric sarcomas must be tailored to the particular tissue type [1,3,6].…”
Section: Introductionmentioning
confidence: 99%